Digital audio forensics fundamentals : from capture to courtroom - Zjalic, James (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Digital Audio Forensics Fundamentals offers an accessible introduction to both the theory and practical skills behind this emerging field of forensic science. Beginning with an overview of the history of the discipline, the reader is guided through forensic principles and key audio concepts, before being introduced to practical areas such as audio enhancement, audio authentication and the presentation of reports. Covering all aspects of audio forensics from the capture to the courtroom, Digital Audio Forensics Fundamentals is pivotal reading for beginners entering the field, as well as experienced professionals looking to develop their knowledge of the practice"--
Introduction -- History of audio forensics -- Forensic principles -- Human auditory system -- Key audio principles -- Audio encoding -- Preparatory analysis -- Audio acoustics -- Speech forensics -- Audio enhancement -- Audio authentication -- Forensic reporting -- Research.
OCLC-licensed vendor bibliographic record.
Keywords: Forensic acoustics; Digital forensic science; Acoustical engineering; Speech processing systems